2016
DOI: 10.1021/acs.inorgchem.6b00168
|View full text |Cite
|
Sign up to set email alerts
|

Roots of Acetate-Vanadium Linkage Isomerism: A QTAIM Study

Abstract: The possibility of linkage isomerism in a number of vanadium(IV) and vanadium(V) complexes with acetate was surveyed using Density Functional Theory (DFT) and Bader's Quantum Theory of Atoms in Molecules (QTAIM). The results show that vanadium-acetate linkages may be classified as bidentate symmetrical, bidentate asymmetrical, or monodentate, the latter being observed in about 40% of the cases. These latter ones correspond to situations where the two oxygen atoms of the acetate moiety are not equivalent. They … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 53 publications
1
15
1
Order By: Relevance
“…The results from both Natural and QTAIM population analysis are in excellent accordance, as expected from previous comparative studies . The QTAIM atomic populations ( NnormalΩ) of N (1) , N (2) , F (3) , and F (4) reflect the expected effect of tinkering with the nuclear charges of each system: atoms for which the nuclear charge was greater than the one found in nature are more electronegative and capable of withdrawing more electron density from their neighbors.…”
Section: Resultssupporting
confidence: 85%
“…The results from both Natural and QTAIM population analysis are in excellent accordance, as expected from previous comparative studies . The QTAIM atomic populations ( NnormalΩ) of N (1) , N (2) , F (3) , and F (4) reflect the expected effect of tinkering with the nuclear charges of each system: atoms for which the nuclear charge was greater than the one found in nature are more electronegative and capable of withdrawing more electron density from their neighbors.…”
Section: Resultssupporting
confidence: 85%
“…The relatively large dispersion of E Mol /n electrons shown in Figure 5a is justifiable by the relatively small impact the iVSCC should have on the potential felt by the electrons in the atomic basins pertaining to the ligands of each TM complex. Although relying on a local adherence to the virial theorem, the negative value of the electronic kinetic energy in the metal basin, −K(M), is a suitable surrogate for contribution of the metal's population to the electronic energy of the molecule, specially when considering general trends in the data 30,40 .…”
Section: Resultsmentioning
confidence: 99%
“…These observations had lead to the conclusion that the penultimate shell (usually referred to as the inner-Valence Shell, iVS) of the metal center of a TM complex is not isotropic and that the molecular geometry in these complexes is dictated by the lowering of the repulsion among these iVS Charge Concentrations (iVSCC) that lie opposite to each ligand. [26][27][28] More recently, a detailed analysis of several vanadium-acetate complexes under the more framework of the Quantum Theory of Atoms in Molecules (QTAIM) has revealed some important exceptions of Gillespie's observations 30 . Although vanadium-acetate complexes in which acetate behaved as a mono-dentate ligand usually conformed to Gillespie's observations, the ones with at least one bidentate acetate ligand did not.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we also employed NBO methodology to elucidate whether the Zn ( Figure 5). The values of the second order stabilization energy ∆E (2) and also the difference between (Zn2) and 3d z 2 (Zn2) → σ* (Zn1) were stabilized by ∆E (2) of 0.93 and 0.96 kcal mol −1 , respectively them were very small, which ruled out the existence of metallophilic interactions between the zinc atoms [87][88][89]. Hence, the small values of ∆E (2) indicated that the Zn•••Zn interaction was attractive and dispersive in nature.…”
Section: Natural Population Analysismentioning
confidence: 96%